Ultra-broadband EPR spectroscopy in field and frequency domains. Issue 22 (29th May 2018) - Neugebauer, P.; Bloos, D.; Marx, R.; Lutz, P.; Kern, M.; Aguilà, D.; Vaverka, J.; Laguta, O.; Dietrich, C.; Clérac, R.; van Slageren, J.
Abstract : Electron paramagnetic resonance (EPR) is a powerful technique to investigate the electronic and magnetic properties of a wide range of materials. Abstract : Electron paramagnetic resonance (EPR) is a powerful technique to investigate the electronic and magnetic properties of a wide range of materials. We present the first combined terahertz (THz) field and frequency domain electron paramagnetic resonance (HFEPR/FDMR) spectrometer designed to investigate the electronic structure and magnetic properties of molecular systems, thin films and solid state materials in a very broad frequency range of 85–1100 GHz. In this paper, we show high resolution frequency-field (Zeeman) maps (170–380 GHz by 0–15 T) recorded on two single-molecule magnets, [Mn2 (saltmen)2 (ReO4 )2 ] and [Mn2 (salpn)2 (H2 O)2 ](ClO4 )2, which give direct access to the field-dependence of the energy level diagram. Furthermore, supression of standing waves in the described system and the sensitivity in field and frequency domain operations is evaluated and discussed.